Analisis Pengaruh Motivasi Kerja Gaya Kepemimpinan Demokratis Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Kejaksaan Negeri Alor - Peny, Theresia Lounggina Luisa; Perseveranda, M E; Hina, Hermyn B. (Jurnal Ilmiah Wahana Pendidikan, 2025)
The performance of employees at the Alor District Attorney's Office is reflected in their abilities and potential in carrying out their work and fulfilling their responsibilities. This study aims to determine the influence of work motivation, democratic leadership style, and organizational culture on employee performance at the Alor District Attorney's Office. This study uses a quantitative descriptive approach. The sample size was 37 employees. Data collection tools included observation, interviews, questionnaires, and literature review. The data analysis models used to answer the hypotheses were multiple linear regression with the t-test to answer the first, second, and third hypotheses. Simultaneous multiple regression analysis, or the F-test, was used to test the fourth hypothesis, which was to determine the effect of work motivation, democratic leadership style, and organizational culture simultaneously on employee performance at the Alor District Attorney's Office. The results of the hypothesis testing proposed in this study are as follows: There is an influence of work motivation, democratic leadership style, and organizational culture on employee performance at the Alor District Attorney's Office.